Bacteremia after Endoscopic Submucosal Excavation for Treating the Gastric Muscular Layer Tumors - Guohua Li; Sheng Zeng; Youxiang Chen; Xiaojiang Zhou; Nonghua Lv (Gastroenterology Research and Practice)
Background. The bacteremia is reported as being infrequent and transient in gastric EMR and ESD for treating gastric mucosa lesions or superficial gastric neoplastic lesion. There was no report of it being investigated in ESD for treating gastric muscular layer tumors (endoscopic submucosal excavation, ESE). This study aimed to determine the frequency of bacteremia in gastric ESE. Patients and Methods. A prospective study, in 122 consecutive patients who underwent gastric ESE for treating gastric muscular layer tumors, investigated the frequency of bacteremia before and 15 minutes after the procedure. Results. The median time for the total ESE procedure was 29 min (range from 8 to 62 min). The mean size of the biggest diameter of each resected specimen was 10±2.7 mm (range from 5 mm to 30 mm). Blood cultures obtained before ESE were positive in 0% (0/122) of cases. Blood cultures obtained 15 min after ESE were positive in 2.5% (3/122) of cases. Six blood samples contained Staphylococcus with coagulase negative, which was considered contaminant. No signs of sepsis were seen in all patients. Conclusions. The frequency of bacteremia after gastric ESE was low. ESE for treating gastric lesions is thought to have a low risk of infectious complications; therefore, prophylactic administration of antibiotics may not be warranted.